Ambient ultrafine particle concentrations and incidence of childhood cancers. (December 2020) - Lavigne, Eric; Lima, Isac; Hatzopoulou, Marianne; Van Ryswyk, Keith; van Donkelaar, Aaron; Martin, Randall V.; Chen, Hong; Stieb, David M.; Crighton, Eric; Burnett, Richard T.; Weichenthal, Scott
Abstract: Background: Ambient air pollution has been associated with childhood cancer. However, little is known about the possible impact of ambient ultrafine particles (<0.1 μm) (UFPs) on childhood cancer incidence. Objective: This study aimed to evaluate the association between prenatal and childhood exposure to UFPs and development of childhood cancer. Methods: We conducted a population-based cohort study of within-city spatiotemporal variations in ambient UFPs across the City of Toronto, Canada using 653, 702 singleton live births occurring between April 1, 1998 and March 31, 2017. Incident cases of 13 subtypes of paediatric cancers among children up to age 14 were ascertained using a cancer registry. Associations between ambient air pollutant concentrations and childhood cancer incidence were estimated using random-effects Cox proportional hazards models. We investigated both single- and multi-pollutant models accounting for co-exposures to PM2.5 and NO2 . Results: A total of 1, 066 childhood cancers were identified. We found that first trimester exposure to UFPs (Hazard Ratio (HR) per 10, 000/cm 3 increase = 1.13, 95% CI: 1.03–1.22) was associated with overall cancer incidence diagnosed before 6 years of age after adjusting for PM2.5, NO2, and for personal and neighborhood-level covariates. Association between UFPs and overall cancer incidence exhibited a linear shape. No statistically significant associations were found for specific cancer subtypes. Conclusion: Ambient UFPs may represent a previously unrecognized risk factor in the aetiology of cancers in children. Our findings reinforce the importance of conducting further research on the effects of UFPs given their high prevalence of exposure in urban areas.